A Comparative Study of Immunohistochemical Expression of BAX Protein in Radicular Cyst and Keratocystic Odontogenic Tumor - Shima Nafarzadeh; Ahmad Reza Sarrafan; Hamid Abbaszadeh Bidokhti; Hemat Gholinia (Islamic Dental Association of Iran, 2015)
Background and Aim: Keratocystic odontogenic tumor (KCOT), formerly known as odontogenic keratocyst (OKC), is a developmental odontogenic cyst with an invasivebehavior and high recurrence rate. Radicular cyst (RC) is an inflammatory non-invasive dental cyst, with no tendency to recurrence. Bcl2-associated X (BAX) protein acts as an apoptotic activator (pro-apoptotic protein), disrupts the integrity of mitochondrial membrane, and leads to the loss of outer membrane and release of cytochrome c from the inner membrane into the cytosol. Since KCOT is more aggressive and has a greater tendency to recurrence than RC, the aim of this study was to assess the immunohistochemical expression of BAX protein in the epithelial lining of RC and KCOT. Materials and Methods: In this descriptive analytical study, paraffinized blocks of 17 RCs and 17 KCOTs fixed in 10% formalin were used (all KCOT samples were non-inflammatory and non-syndromic). After confirming the diagnoses by reviewing the slides, tissuespecimens with sufficient length of epithelium were stained by immunohistochemistry (IHC) for BAX marker. Then, the stained cells were randomly counted in five high power fields. Analysis of the data was performed using SPSS 21 via Student's t-test and chi-test. Results: Percentages of staining for BAX marker were 16.4±9.4% and 66.4±12.3% in the epithelial lining of KCOT and RC, respectively and there was a significant difference between them (P<0.001). Conclusion: According to the findings, lower expression of BAX protein in KCOT justifies its more aggressive behavior and tendency to recurrence compared to RC.